2021
DOI: 10.1002/hbm.25359
|View full text |Cite
|
Sign up to set email alerts
|

The variability of MR axon radii estimates in the human white matter

Abstract: The noninvasive quantification of axonal morphology is an exciting avenue for gaining understanding of the function and structure of the central nervous system. Accurate non‐invasive mapping of micron‐sized axon radii using commonly applied neuroimaging techniques, that is, diffusion‐weighted MRI, has been bolstered by recent hardware developments, specifically MR gradient design. Here the whole brain characterization of the effective MR axon radius is presented and the inter‐ and intra‐scanner test–retest rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 92 publications
2
37
0
Order By: Relevance
“…The first and fundamental determinant is the axonal diameter, as in myelinated axons conduction velocity is proportional to the inner (i.e., without accounting for the myelin sheath) diameter. Using diffusion MRI and ultra-high gradients (Huang et al, 2020;Jones et al, 2018), it is possible to estimate the axonal diameter in the human brain (at least for the largest ones), and recent studies have shown measures in line with the underlying histology (Huang et al, 2020;Veraart et al, 2020) and with good scan-rescan reliability (Veraart et al, 2021). Another important determinant of conduction velocity is the myelin content.…”
Section: Introductionmentioning
confidence: 99%
“…The first and fundamental determinant is the axonal diameter, as in myelinated axons conduction velocity is proportional to the inner (i.e., without accounting for the myelin sheath) diameter. Using diffusion MRI and ultra-high gradients (Huang et al, 2020;Jones et al, 2018), it is possible to estimate the axonal diameter in the human brain (at least for the largest ones), and recent studies have shown measures in line with the underlying histology (Huang et al, 2020;Veraart et al, 2020) and with good scan-rescan reliability (Veraart et al, 2021). Another important determinant of conduction velocity is the myelin content.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in section 2.5, we have shown how a distribution of diameters projects itself onto a single fitted effective diameter. The effective diameter can be estimated reliably using advanced hardware and dedicated sequences [52,53] but still display the same insensitivity to small and medium axons and unresolvability of distribution shape. Nevertheless, the effective diameter is correlated with the biggest axons and differences in these biggest axons might be relevant in some cases such as pathology [53].…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that previous, apparently plausible results arise from some combination of effects outside of the model assumptions that are projecting themselves onto the model parameters in a complex way. Admittedly, some parameters can be reliably fitted to the data, such as the effective diameter [52,53], if an appropriate sequence and method are used to suppress the extra-axonal signal contribution. As we have demonstrated, In the simulations, we considered that the typical white matter SNR from an MR acquisition using Connectom gradients was driven only by the intra-axonal compartment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations